Experience of the Implementation of the Modular Principle in the Training of Primary School Teachers - Budnikova S.P (Moscow State University of Psychology and Education, 2020)
The article presents the results of participation of the Tula State Lev Tolstoy Pedagogical University in the second and third stages of approbation of the basic professional educational program in terms of education bachelor degree with the direction: 44.03.05 "Pedagogical education (with two profiles of preparation)", profiles of preparation: Primary education, Foreign language; Primary education, Informatics. This project was implemented on the basis of an agreement on network interaction concluded with MSUPE. Approbation was attended by students 4 and 5 courses. The content, the course of implementation and the main results that were achieved by the students in the course of approbation and the formation of their professional subjectness were analyzed. The results of the pilot approbation of the toolkit of independent evaluation of the formation of the general professional competencies of students are also considered. The difficulties that were discovered during the practice process were classified. The project was tested within the framework of the Federal target program of education development for 2016-2020.